An Ecosocial Frame for Autonomous Vehicles. Issue 4 (2nd October 2019) - Martin, George
ABSTRACT: This paper analyses ecosocial parameters for the coming of autonomous vehicles—a subject obscured by their technological and business prospects. The world's largest multinational digital and automotive corporations are making massive investments in the autonomous vehicle roll-out. As is usually the case with a new technological consumer product, discourse centers on its promises, not its perils. Largely ignored are potential impacts on social justice and environmental sustainability. This critical framing can be a basis for developing an ecosocial presence in the expanding autonomous vehicle discourse, as well as in the emergent politics of its deployment.